Comparative Study for the Effect of Biofertilizers and Chemical Fertilizers on Soybean Oil Content and its Potential for Biodiesel Production: Effect of Fertilizers on Soybean Oil Content - Bano, Asghari; Nosheen, Asia; ullah, Faizan (Biological Sciences - PJSIR, 2009)
The present study makes comparative evaluation of biofertilizers (brands Biopower and Biozote) and chemical fertilizers (urea and diamonium phosphate (DAP)) on yield and the quality of soybean cv.NARC-1. Signifi- cant increase in number of pods per plant, seed oil content and specific gravity of oil was observed in case of chemical fertilizer treatment. All the treatments decreased the acid value and free fatty acid (oleic acid) content of oil, maximum reduction being in the case of Biopower treatment. Biopower treated plant seed oil exhibited higher refractive index and maximum conversion to methyl esters/biodiesel.